Oxidative Stress and Hyper-Inflammation as Major Drivers of Severe COVID-19 and Long COVID: Implications for the Benefit of High-Dose Intravenous Vitamin C - Vollbracht, Claudia; Kraft, Karin (Frontiers in Pharmacology, 2022)
Oxidative stress is a pivotal point in the pathophysiology of COVID-19 and presumably also in Long-COVID. Inflammation and oxidative stress are mutually reinforcing each other, thus contributing to the systemic hyperinflammatory state and coagulopathy which are cardinal pathological mechanisms of severe stages. COVID-19 patients, like other critically ill patients e.g. with pneumonia, very often show severe deficiency of the antioxidant vitamin C. So far, it has not been investigated how long this deficiency lasts or whether patients with long COVID symptoms also suffer from deficiencies. A vitamin C deficit has serious pathological consequences because vitamin C is one of the most effective antioxidants, but also co-factor of many enzymatic processes that affect the immune and nervous system, blood circulation and energy metabolism. Because of its anti-oxidative, anti-inflammatory, endothelial-restoring, and immunomodulatory effects the supportive intravenous (iv) use of supraphysiological doses has been investigated so far in 12 controlled or observational studies with altogether 1578 inpatients with COVID-19. In these studies an improved oxygenation, a decrease in inflammatory markers and a faster recovery were observed. In addition, early treatment with iv high dose vitamin C seems to reduce the risks of severe courses of the disease such as pneumonia and also mortality. Persistent inflammation, thrombosis and a dysregulated immune response (auto-immune phenomena and/or persistent viral load) seem to be major contributors to Long-COVID. Oxidative stress and inflammation are involved in the development and progression of fatigue and neuro-psychiatric symptoms in various diseases by disrupting tissue (e.g. autoantibodies), blood flow (e.g. immune thrombosis) and neurotransmitter metabolism (e.g. excitotoxicity). In oncological diseases, other viral infections and autoimmune diseases, which are often associated with fatigue, cognitive disorders, pain and depression similar to Long-COVID, iv high dose vitamin C was shown to significantly relieve these symptoms. Supportive iv vitamin C in acute COVID-19 might therefore reduce the risk of severe courses and also the development of Long-COVID.